Physical and Biogeochemical Properties of Rotten East Antarctic Summer Sea Ice - Corkill, M.; Moreau, S.; Janssens, J.; Fraser, A. D.; Heil, P.; Tison, J.-L.; Cougnon, E. A.; Genovese, C.; Kimura, N.; Meiners, K. M.; Wongpan, P.; Lannuzel, D. (Journal of Geophysical Research: Oceans, 2023)
Sea ice forms a barrier to the exchange of energy, gases, moisture and particles between the ocean and atmosphere around Antarctica. Ice temperature, salinity and the composition of ice crystals determine whether a particular slab of sea ice is habitable for microorganisms and permeable to exchanges between the ocean and atmosphere, allowing, for example, carbon dioxide (CO2) from the atmosphere to be absorbed or outgassed by the ocean. Spring sea ice can have high concentrations of algae and absorb atmospheric CO2. In the summer of 2016?2017 off East Antarctica, we found decayed and porous granular ice layers in the interior of the ice column, which showed high algal pigment concentrations. The maximum chlorophyll a observed in the interior of the ice column was 67.7 ?g/L in a 24% porous granular ice layer between 0.8 and 0.9 m depth in 1.7 m thick ice, compared to an overall mean sea-ice chlorophyll a (± one standard deviation) of 13.5 ± 21.8 ?g/L. We also found extensive surface melting, with instances of snow meltwater apparently percolating through the ice, as well as impermeable superimposed ice layers that had refrozen along with melt ponds on top of the ice. With future warming, the structures we describe here could occur earlier and/or become more persistent, meaning that sea ice would be more often characterized by patchy permeability and interior ice algal accumulations.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; biogeokjemi; havis; isfjell